Synthesis and characterization of Fe-doped CuO nanoparticles: Catalytic efficiency in crystal violet dye degradation and exploration of electrical properties - Bushra; Kashif, Muhammad; Khairullah; Khan, Azmat Ali; Sun, Hao; Yousaf, Jasim; Shah, Muhammad Ishaq Ali; Hussain, Shah; Amir, Jalal; Jamal, Yousaf; Ahmad, Taimoor (Brazilian Journal of Science, 2024)
In recent times, environmental pollution has become a pressing issue. Different methods have been developed to detach hazardous materials from H2O bodies. Among these techniques, photo-catalysis has emerged as a low-cost and advanced method. However, finding a potent photocatalyst has been a topic of considerable research. Our study prepared CuO from copper acetate using hydrothermal treatment in an autoclave at 170 ºC for 14 hours. We introduced various quantities of Fe by adding FeSO4 mixture to Cu (CH3COO)2, following the identical method for preparing CuO. The resulting precipitate was cleaned with deionized H2O and dried at 100 °C. The prepared substance was then heated at 450 ºC in a muffle furnace for 60 minutes. We characterized the manufacture of photocatalysts utilizing various techniques such as Ultraviolet (UV), FT-IR, SEM, EDX, and XRD. Our Ultraviolet (UV) spectrum analysis helped us recognize the adsorption spectroscopic analysis of un-doped and doped CuO with various ratios of Fe. FTIR spectroscopic analysis helped us identify functional groups in CuO NPs. Our XRD study showed the monoclinic composition of copper oxide nanoparticles. The SEM picture suggested that NPs exist in a spherical shape. We studied the catalytic activity of synthesized NPs concerning crystal violet (CV) colorant degradation below a direct ray of light irradiation. Our results showed that the degradation productiveness, as compared to CV colorant, was about 93.52% in 180 min. This research is of great importance in the quest for effective and sustainable solutions to environmental problems. The examination of electrical properties highlighted the promising aspects of Fe-doped CuO, particularly at 6% doping. This variant demonstrated superior dielectric parameters, lower tangent loss, semiconductor-like impedance behavior, and enhanced electrical conductivity, emphasizing its potential for applications in electrical and energy storage domains.